1971
DOI: 10.1126/science.172.3988.1159
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical Fluorescence of Raphe Neurons: Selective Enhancement by Tryptophan

Abstract: The histochemical fluorescence of those neurons in brainstem raphe nuclei which are presumed to contain serotonin is selectively and stereospecifically enhanced by L-tryptophan at doses that also produce an elevation in the concentration of serotonin. However, contrary to our assumptions, the increase in raphe fluorescence is not prevented by p-chlorophenylalanine, an inhibitor of serotonin synthesis. These results suggest that under some conditions derivatives of tryptophan other than, or in addition to, sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

1972
1972
1984
1984

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…Even following a tryptophan loading sched ule, as described by Aghajanian and Asher (1971), which greatly enhances the concentra tion of fluorescence in the raphe system of the brain stem, we could not detect 5-MT with our methods. This does not support the hypothesis that 5-MT is the identity of the B-type fluo rophore as suggested by Green et al (1973) and Koslow (1974).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Even following a tryptophan loading sched ule, as described by Aghajanian and Asher (1971), which greatly enhances the concentra tion of fluorescence in the raphe system of the brain stem, we could not detect 5-MT with our methods. This does not support the hypothesis that 5-MT is the identity of the B-type fluo rophore as suggested by Green et al (1973) and Koslow (1974).…”
Section: Discussionmentioning
confidence: 52%
“…These authors have defined this amine as a 'B-type' fluorophore and have differ entiated it by microspectrofluorimetry from other fluorophores produced by the catechol amines and serotonin (Bjorklund et al, 1971b). Aghajanian and Asher (1971) have shown that after a tryptophan preload there is an increase in fluorescence in the raphe nuclei of the mes encephalon both in terms of numbers of cells and brilliance of reaction. This increase in fluo rescence is resistant to p-chlorophenylalanine (PCPA) treatment (which lowers brain 5-HT).…”
mentioning
confidence: 99%
“…The intensity as well as the number of fibres that exhibited serotonin-like immunoreactivity was less conspicuous in the ganglion without pre-treatment with tryptophan; the reason for this is not clear. In this context, the serotonin histofluorescence of the central (Aghajanian & Asher, 1971) and enteric (Dreyfus, Bornstein & Gershon, 1977) neurones was also shown to be markedly enhanced by pre-loading the animals with the precursor. As the serotonin-like immunoreactivity could be traced along the nerve fibres that enter the ganglion, the origin of these fibres is of interest.…”
Section: Discussionmentioning
confidence: 99%
“…(1965) and Collard & Roberts ( 1974) measured the accumulation of 5-HT in the brain by chemical estimation. The increase of 5-HT in such experiments in the 5-HT containing neurone system was described by Aghajanian & Asher (1971), Aghajanian, Kuhar & Roth (1973) and also after treatment with 5-hydroxytryptophan (the precursor of 5-HT) an increase of fluorescence in various structures in rat brain was shown by Fuxe (1965). Due to non-specific uptake, 5-HT can also be found in areas normally containing only catecholamines (Bertler etal., 1964;Fuxe etal., 1971;Butcher et al, 1972;Dow & Laszlo, 1976).…”
Section: Discussionmentioning
confidence: 99%